Combining current knowledge of Cypripedium calceolus with a new analysis of genetic variation in Italian populations to provide guidelines for conservation actions. Issue 10 (27th August 2021) - Gargiulo, Roberta; Adamo, Martino; Cribb, Phillip J.; Bartolucci, Fabrizio; Sarasan, Viswambharan; Alessandrelli, Claudia; Bona, Enzo; Ciaschetti, Giampiero; Conti, Fabio; Di Cecco, Valter; Di Martino, Luciano; Gentile, Carmelo; et al.
Abstract: The split between conservation science and real‐world application is an ongoing issue despite several calls for unification. Researchers are empowered to partially bridge the research‐implementation gap by making their findings more accessible. Cypripedium calceolus is the most recognizable orchid of the European flora, and is currently facing habitat change and fragmentation, in addition to threats from collectors and illegal traders. Although several studies have focused on the ecological and genetic features of the species, a comprehensive account of how such aspects can be translated into concrete conservation recommendations is still missing. In this study, we describe microsatellite genetic variation in 188 individuals from different Italian populations of C. calceolus . Our results indicate the need for immediate conservation action for the most isolated populations in the Central Apennines and north‐western Italy. Although our genetic findings are specific to the Italian populations, our aim is to review ecological and population genetic aspects in C. calceolus and their implications for conservation against the existing threats. Therefore, our detailed guidelines for translocation, habitat management and post‐translocation monitoring can be used to inform conservation strategies in threatened populations of C. calceolus across its range.